Evaluasi Pemasangan Barrier System di Desa Bener Kecamatan Wonosari Kabupaten Klaten - Titah Nurhawati; Bonjok Istiaji; Swastiko Priyambodo (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Rats are pests that are difficult to control because they attack plants on various stages of storage. Control of mice in the paddy ecosystem can be done by the Trap Barrier System (TBS). This study aims to evaluate the installation of the Barrier System in Bener Village, Wonosari District, Klaten Regency, Central Java. The study was conducted by the method of field observation, interviews, and literature studies. The results showed that the installation of the Barrier System in Bener Village was ineffective due to the lack of farmers' attention to the components of FFB and the lack of support from farmers. Keywords: rats, rat control, trap barries system (TBS)